The Interpretation of Tropical Architecture in Designing Culinary and Music Centre in Medan - Olivia Natania Sembiring Meliala; Dwira Nirfalini Aulia (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The design of a creative industry development center that focuses on the culinary and music subsectors aims to facilitate the growth and development of creative industry players in these two subsectors, so that they can contribute positively to the local economy. The facilities in this center will be designed to meet the needs of production, training, exhibition, and sales in the culinary and music subsectors. It is expected that the design of the Creative Industry Development Center will encourage local economic growth, create new jobs, improve the skills of industry players, and support the image of Medan City as a quality creative industry center. By connecting the culinary and music subsectors in one center, the synergy between the two can produce unique and inspiring collaborations, enrich local culture, and present products that are competitive in the global market. By applying a tropical architecture approach, the design will consider aspects of local culture, climate, and environment in designing optimal buildings and spaces to support the growth of creative industries.